Analisis peran guru dalam mengimplementasikan pendidikan karakter disiplin peserta didik kelas VI A SDN 3 Tugu Kecamatan Cihideung - Rismawati, Ima; Rakhmat, Cece; Nugraha, Fajar (COLLASE (Creative of Learning Students Elementary Education), 2025)
Abstract Schools as a place to realize national education goals have an important role in educating the character of students. The task of teachers in schools is not only to teach related knowledge but also to shape students' attitudes and behavior, one of which is disciplinary character. The purpose of this research is to determine student discipline and the role of teachers in disciplining students. The method used in this research is a descriptive qualitative method. Data collection techniques were obtained through interviews, observation and documentation. Based on research results, student discipline is in the medium category, where students are still not completely orderly during the learning process, such as liking to chat and joke, and when obeying rules, such as not implementing class rules. The teacher's task in disciplining students is to familiarize themselves with order in every activity carried out at school, such as being solemn during the flag ceremony, and praying before and after studying. The role of the teacher in carrying out this task is as a role model, the teacher provides an example in punctuality, how to dress, as well as in behavior and speech. As a supervisor, the teacher directs/guides students to be able to comply with every activity carried out at school. And as a motivator, teachers provide advice and encouragement to students in learning and outside of learning. Keywords: Teacher's Role, Implementation, Student Discipline Abstrak Sekolah sebagai tempat mewujudkan tujuan pendidikan nasional mempunyai peran penting dalam mendidik karakter peserta didik. Tugas guru di sekolah tidak hanya mengajarkan terkait dengan pengetahuan saja tetapi juga dapat membentuk sikap dan perilaku peserta didik, salah satunya karakter disiplin. Tujuan dari penelitian ini untuk mengetahui kedisiplinan peserta didik serta peran guru dalam mendisiplinkan peserta didik. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Teknik pengumpulan data diperoleh melalui wawancara, observasi serta dokumentasi. Berdasarkan hasil penelitian kedisiplinan peserta didik berada pada kategori sedang, dimana peserta didik masih belum sepenuhnya tertib saat proses pembelajaran seperti suka mengobrol dan bercanda, serta saat mematuhi peraturan seperti tidak melaksanakan tata tertib kelas. Tugas guru dalam mendisiplinkan peserta didik yaitu dengan membiasakan tertib pada setiap kegiatan yang dilaksanakan di sekolah, seperti khidmat saat upacara bendera, dan berdoa sebelum dan sesudah belajar. Adapun peran guru dalam melaksanakan tugas tersebut yaitu sebagai teladan guru memberikan contoh dalam ketepatan waktu, cara berpakain, serta dalam bersikap dan bertutur kata. Sebagai pembimbing guru mengarahkan/membimbing peserta didik untuk dapat mematuhi setiap kegiatan yang dilaksanakan di sekolah. Dan sebagai motivator guru memberikan nasihat dan semangat kepada peserta didik dalam belajar juga di luar pembelajaran. Kata Kunci: Peran Guru, Implementasi, Disiplin peserta didik.